Traditional Versus Rapid Internationalization of High-Tech firms. Results of Investigation - Nelly Daszkiewicz (Problemy Zarządzania, 2017)
The discussion on the role and importance of time in the process of internationalization of firms belongs to the mainstream of research in the field of internationalization. In the literature, the phenomenon of early and rapid internationalization was noticed in the early 1980s; however, the intensive development of the research into this phenomenon began a decade later and continues today. For several years in Poland, the share of early internationalized firms has been growing. These firms start their international activities almost from their inception. The main objective of the article is to present the pace of the internationalization process of firms from the perspective of two major theoretical approaches and its empirical verification. The article includes the literature review as well as the results of a survey conducted among 263 high-tech production firms from Poland. In the summary of the article, future directions of research are pointed out.